Information relevance of agricultural articles in malayalam newspapers and farm magazines - a multi-dimensional analysis - Suresh kumar S (Department of Agricultural Extension, College of Agriculture, 2007)
The study entitled “Information relevance of agricultural articles in newspapers and farm magazines” was undertaken to assess the relevance or pertinence of information passed on to farmers through the farm pages of selected Malayalam newspapers and farm magazines. It was also aimed to delineate the factors that influence the information relevance and to identify which of them were influencing the relevance of information to a greater extent.